Material removal mechanism of copper chemical mechanical polishing with different particle sizes based on quasi-continuum method - Aibin Zhu; Dayong He; Shengli He; Wencheng Luo (Friction)
Abstract In this paper, the material removal mechanism of copper chemical mechanical polishing was studied by the quasicontinuum method that integrated molecular dynamics and the finite element method. By analyzing the abrasive process of different particle sizes on single crystal copper, we investigated the internal material deformation, the formation of chips, the stress distribution, and the change of cutting force. Results showed that shear band deformation was generated along the cutting direction at approximately 45° inside the workpiece material. The deformation was accompanied by dislocations and sliding phenomena in the shear band region. Smaller abrasive particle size led to poor quality of the workpiece, while a larger particle size led to better quality. However, larger particle size resulted in greater plastic deformation and deeper residual stress inside the workpiece. Size change of abrasive particles had little effect on the tangential cutting force.